Analisa Pengaruh Luasan Cell terhadap Efisiensi dan Volume Hidrogen pada Generator HHO menggunakan Larutan Air - Setiyawan, Catur Heri; Soebiyakto, Gatot; Ismail, Nova Risdianto (Widyagama University of Malang, 2023)
The availability of fossil fuels is becoming increasingly limited due to increased innovation in transportation technology resulting in an increase in the number of motor vehicles. The combustion of fossil fuels also has an impact on the environment, such as increasing global warming. This study aims to determine the volume of hydrogen and the flame profile if the plate area is varied. The test was conducted experimentally using 1.3 liters of water. P X L electrodes have sizes (12.5cm x 2.5cm), (11.5cm x 2cm), (10.5cm x 1.5cm), and (10cm x 1 cm). Tests include HHO generator efficiency tests. The test results show that the largest gas production rate occurs in the area of P X L (12.5cm x 2.5cm), producing a volume of 60 ml with a time of 30 seconds and a production rate of 0.002 l/s. The best HHO generator efficiency is obtained at an area of P X L (12.5cm x 2.5cm) of 32.53%.